A qualitative analysis of intravenous smart pump usability - Jeannine W. C. Blake; Sarah M. Fiske; Karen K. Giuliano (Wiley, 2022)
Abstract Aim To understand the experience of critical care nurses when performing common, yet error‐prone, programming tasks on two unfamiliar intravenous smart pumps. Design A qualitative descriptive study using data collected during a previous quantitative pilot study. Methods Following completion of common intravenous programming tasks each participant was interviewed using a semi‐structured interview guide. All interview data were coded line‐by‐line and thematic analysis revealed themes across all participants' interviews. Results The following four themes were identified: appreciation for attractive design features, the need for efficiency, the importance of intuitive use and concern for patient outcomes. Overall, these themes provide evidence that nurses strongly prefer a more usable intravenous smart pump interface that integrates safeguards to efficiently improve patient outcomes. Findings support the need for intravenous smart pump technology to be developed with an intuitive interface that decreases the level of cognitive demand and will lead to improved patient safety.